Plasmid profile analysis and curing of plasmids in Enterobacteriaceae isolated from patients of Urinary Tract infection - Haque, S.A.M. Salman (BRAC Univeristy, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2018.